FEATURES OF EFFECTIVE MANAGEMENT OF SOCIAL RESPONSIBILITY OF TRADE ENTERPRISES IN THE CONDITIONS OF QUARANTINE AND COVID-19 SPREAD - GARAFONOVA, OLGA; BILOUS, ANNA; YASHCHENKO, INNA; MARHASOVA, OLHA; DYKHNYCH, LIUDMYLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Covering all continents and countries, for two years in a row, the problem of COVID-19 remains one of the largest in the world, despite active opposition to the spread of the virus. Its influence extends not only to individuals but also to the entire population, especially to the business sector of different countries, and the scale is gaining momentum. Businesses go bankrupt and people close, people lose their jobs, and others have to adapt quickly to new demands from management or government agencies for fear of losing their jobs or wages. At this time, the number one priority remains the safety of life and health of the population. Despite the daily coverage of the COVID-19 pandemic on all continents, this is the best time to work together (following the methods of social distance and the recommendations of health workers) to save the people and the economy. In today's world, businesses must not only strive for high financial performance, but also benefit society and the well-being of stakeholders: partners, families, employees, customers and the community. In addition, the important task of management is to identify and outline a list of aspects that will help in the remote work process for both the manager and his subordinates to effectively perform their job functions and responsibilities.The article is devoted to the components of effective management of corporate social responsibility during the quarantine and Covid-19 spread. The article defines the phenomenon of corporate social responsibility, emphasizes its importance during the pandemic. The article analyzes and provides statistics related to the spread of Covid-19, presents foreign and domestic experience of trade enterprises in disseminating the principles of corporate social responsibility, presents main elements and difficulties of remote work, provide graphs for better information understanding. Furthermore, it identifies the features of management that focuses on the concept of social responsibility of the enterprise, applied to the employees and society as a whole during quarantine, identifies the factors that managers should pay attention to while managing workers process.
Keywords: corporate social responsibility; CSR; charity; Covid-19; quarantine; remote working process; effective management